KEBIJAKAN RUANG PUBLIK PEREMPUAN DI SAUDI ARABIA: Benarkah Sebuah Agenda Politik Double Interest? - Fatkhur Roji (International Journal Ihya' 'Ulum al-Din, 2017)
The emergence of the Saudi government's policy of allowing women to drive alone these days has become an interesting phenomenon to be examined, since before they forbid women to drive without a mahram. Since the appointment of the crown prince Salman bin Abdul Aziz, the Saudi government appears more dynamic and moderate. This new policy is in place to promote the development of the country with and to give women the right to participate freely in it. Observers see this as a political agenda of government, where with the political interest is expected Saudi Arabia can compete in the increasingly tight global economic competition. This article examines the policies of the Saudi Arabian government thoroughly from a social, economic, and political standpoint.